Investigation of tobramycin incorporated calcium phosphate beads in preventing methicillin-resistant Staphylococcus aureus induced osteomyelitis in rabbits - Anebow, Lulu Godday (2016)
The persistence rise in bacteria resistant to antibiotics and reoccurrence of infections, has led to the involvement of new aminoglycosides class of antibiotics which serves as a promising alternative to overcome the escalating antibiotic resistance. The aim of this study is to investigate the efficacy of tobramycin beads in preventing osteomyelitis in rabbit model. Tobramycin (30mg/mL) was incorporated into calcium phosphate (CaP) beads, by dipping method as a local drug delivery system. For juxtaposition, beads incorporated with calcium phosphate and tobramycin, and beads incorporated with calcium phosphate alone (without tobramycin, control) were prepared. A total of 20 New Zealand white rabbits were involved. Animals were divided into five groups as follows: group I were the sham (operated but without treatment), group II were inserted with tobramycin incorporated calcium phosphate bead without bacteria inoculums, group III were inoculated with bacteria only, group IV were inserted with calcium phosphate bead and bacteria inoculums, and group V were inserted with tobramycin incorporated calcium phosphate bead with bacteria inoculums. For the groups involving beads implantation, bacterial culture was inoculated immediately after surgery at the mid-shaft of tibia. After 28 days, they were euthanized and the presence or absence of osteomyelitis as well as the extent of the destruction of the bone architecture were investigated by radiology and histology. Microbiological analysis was carried out for the enumeration of bacterial load present in the bone and surrounding tissues. Blood samples were collected before surgery and weekly after surgery for confirmation of infection and inflammation. Hematological counts were analyzed by automated hematology analyzer, while erythrocyte sedimentation rate (ESR) by ESR fast detector. Blood smears were made and blood samples were analyzed through automated hematology analyzer for confirmation of infection. ESR fast detector which reads the rate of inflammation of one hour in 30 min was used to detect the rate of inflammation. Changes in body temperature and weight were also done to see its association with infection. Bone samples were harvested from a transverse saw cut made in the middle of the tibia at the site of infection and the samples were subjected to scanning electron microscope (SEM) to confirm the presence of S. aureus. It was observed by SEM that once inoculation was introduced to the tibia bone, S. aureus at this site of infection started colonization, through a combination of cell division and recruitments, and undergoes changes in shapes and sizes, allowing them to become more resistant to antibiotics and antibodies. Presence of S. aureus colonies was observed within the site of infection and bacterial cells were distributed in numerous ways that permit them to infect new tissues. Tobramycin incorporated with calcium phosphate bead group, potentially minimized bacterial growth in the tibia compared to control group, where there is potential bacterial growth and bone destruction, and there was significant difference between these groups. Chronic osteomyelitis with enhanced bacterial growth and marked changes in the bone architecture were noticed in the group infected with S. aureus. No bacterial growth and pathological changes were noticed in the group implanted with tobramycin-coated CaP without bacteria and the sham group. Hematological parameter showed the presence of infection as well as inflammation in groups III, IV and V respectively. No infection or inflammation was noticed in groups I and II. Hematological parameters especially ESR, is sensitive in detecting inflammation and infection and have good correlation with respond to treatment. Changes in temperature and body weight were not fully correlated with the rate of infection, in confirmation of their relationship to infection and inflammation. In conclusion, SEM observations confirmed the presence of S. aureus in bone samples which further underscores that S. aureus is the major cause of wound suppuration and osteomyelitis formation. Tobramycin incorporated with CaP beads is found to be an effective prophylaxis in this model. CaP bead is an excellent biodegradable biomaterial, especially in local administration/delivery of antibiotics. It is effective in prevention of osteomyelitis in rabbit model and degrades after 28 days. White blood cell (WBC) count and ESR are promising markers of infection and inflammation associated with osteomyelitis formation.